(untitled) (Eurasian Medical Research Periodical, 2023)
The review presents current data on the methods of treatment of myasthenia gravis. The features of the course of myasthenia gravis, their influence on approaches to treatment are highlighted. The features of medical tactics aimed at preventing crises are considered. The issues of the effectiveness of thymectomy and rehabilitation of patients after surgery are highlighted. According to modern concepts, the correct management of patients during and after thymectomy is essential to improve the outcomes of the operation.